2013
DOI: 10.1590/s2317-64312013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Reabilitação auditiva na criança: adesão ao tratamento e ao uso do aparelho de amplificação sonora individual

Abstract: Previously Determined (Families that attend both the speech therapy and the Family Adhesion Group (GrAF) from the first day set for the beginning of sessions, to the last day); Continuous Flow (Families that started attending the group from the moment they arrived for the ADAPTI); and Control (Families that only attended speech therapy, but not the GrAF). Results:The study verified the effectiveness of parent adhesion to their children's treatment with more than 66% of attendance in the proposed activities (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 16 publications
(20 reference statements)
2
10
0
9
Order By: Relevance
“…The results for the educational level of the parents participating in the study -complete High School (36%) for mothers and complete Elementary and Junior High School (24% each) for fathers -are similar to those found by other authors (8,9) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results for the educational level of the parents participating in the study -complete High School (36%) for mothers and complete Elementary and Junior High School (24% each) for fathers -are similar to those found by other authors (8,9) .…”
Section: Discussionsupporting
confidence: 89%
“…Regarding thresholds of children without electronic devices -48% thresholds characteristic of profound hearing loss and 24% thresholds characteristic of severe loss -it was found that similar data has also been raised by other studies in the literature (8,9) .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…After the brainstorming session, modifications were not suggested to ten items (2,3,4,7,12,14,20,21, 27 and 31), while the modifications deemed necessary for 25 items. Items that were the most commented by the parents guided the discussion among experts.…”
Section: Establishment Of Alterations By Item From the Notes Of Parementioning
confidence: 99%
“…Several instruments address the issue of factors that determine auditory and language skills (1,2,3) , many of them individualizing the perception of the family in relation to the child's language development (4,5,6) . The issue of therapeutic fit with infants has also been discussed.…”
Section: Introductionmentioning
confidence: 99%